The Role of the Sense of Community in the Sustainability of Social Network Sites. Issue 4 (1st October 2016) - Mamonov, Stanislav; Koufaris, Marios; Benbunan-Fich, Raquel
ABSTRACT: The evolution of information technologies enables new forms of communication and facilitates the emergence of different types of virtual communities, such as social networks. While some social network services have succeeded, others have failed. Understanding the factors that affect the sustainability of social network sites is important for both research and practice. We draw on the sense of community theory to develop a nomological framework of antecedents and consequences associated with sense of community in social network sites. We evaluate the framework with a survey of 506 Facebook users. We find that sense of community has a strong effect on information consumption and contribution, as well as exit intentions among social network site users, thus highlighting the important role of sense of community in the sustainability of social network sites. We also find that both system-related (sense of place associated with the social networking site) and social (social interaction) factors contribute to the development of sense of community. The nomological framework developed in the current study provides a theoretical foundation that could be adapted to study other factors that influence the development of sense of community across different virtual community contexts.